Rentabilitas Usahatani Jagung di Desa Oenenu Kecamatan Bikomi Tengah Kabupaten Timor Tengah Utara - Ona G. Almet; Maximiliam M. J. Kapa; Ignatius Sinu (Undana Press, 2019)
A Research on the Rentability of Maize Farming in Oenenu Village, Central Bikomi Subdistrict, North Central Timor Regency was carried out from November to December 2018. This study aims to (1) determine the benefits and (2) know the profitability of maize farming in Oenenu Village. The number of samples in this study were 68 respondents. The method of data collection was the survey method. Primary data was obtained from maize farmers through interviews method while secondary data is obtained from agencies related to this study. The collected data was tabulated and analyzed to answer the objectives of the study. Profit analysis was obtained from the difference between the amount of revenue and production costs. While the profitability of own capital was obtained from the comparison between the net income and own capital. The results of the study showeel (1). The average income from maize farming was Rp 3,178,970.59 with the average of production cost was Rp 480,145.05 so that the average profit earned by farmers was Rp 2,698,823.53 and (2) thes Rentability for own capital in the study was 55.60% per planting season. This means that using own capital will provide a profit of 55.60%. Thus, maize farming in Oenenu Village is efficient and feasible. Penelitian tentang Rentabilitas Usahatani Jagung di Desa Oenenu Kecamatan Bikomi Tengah Kabupaten Timor Tengah Utaratelahdilaksanakansejakbulan November sampai dengan Desember 2018. Penelitian ini bertujuan untuk (1) mengetahui keuntungan dan (2) rentabilitas usahatani jagung di Desa Oenenu. Jumlah sampel dalam penelitian ini sebanyak 68 responden. Metode pengumpulan data adalah metode survei. Data primer diperoleh dari petani jagung melalui wawancara sedangkan data sekunder diperoleh dari instansi terkait dengan penelitian ini. Data yang terkumpul ditabulasi dan dianalisis untuk menjawab tujuan dari penelitian. Analisis keuntungan diperoleh dari selisih antara jumlah penerima dan biaya produksi. Sedangkan rentabilitas modal sendiri diperoleh dari perbandingan antara laba bersih dengan modal sendiri. Hasil penelitian menunjukkan (1). Rerata penerimaan dari usahatani jagung adalahRp 3.178.970,59 dengan rerata biaya produksi sebesar Rp 480.147,05 sehingga rerata keuntungan yang diperoleh petani adalah sebesar Rp 2.698.823,53. (2) Rentabilitas atas modal sendiri dalam penelitian adalah 55,60% per musim tanam. Artinya bahwa dengan menggunakan modal sendiri akan memberikan keuntungan sebesar 55,60 %. Dengan demikian usahatani jagung di Desa Oenenu adalah efisien dan layak untuk diusahakan.